Visual Allegories in The Truman Show: A Study of Metaphor, Simile, and Personification - Ibnu Subroto; Retno Rahayuningsih (J-CEKI : Jurnal Cendekia Ilmiah, 2024)
Symbolism in film enhances the story by adding depth and meaning to characters and themes. In The Truman Show, the use of metaphor, simile, and personification helps uncover the deeper symbolism of the film and its broader messages. This research takes a qualitative approach by analyzing the film’s script through content analysis. The process involves outlining the topic, organizing the thesis, gathering information from both the film and online resources, and examining how these symbols contribute to the film’s overall meaning. In the study, the use of personification is found to be the most prominent, making up 41.2% of the instances, followed by metaphor at 35.3%, and simile at 23.5%. These literary devices help to build the narrative and explore important themes, such as the nature of reality, the power of the media, and individual freedom. By using these devices, The Truman Show invites viewers to reflect on how media shapes our perceptions of the world and our sense of self. The film serves as a warning about the dangers of turning real life into entertainment, showing how this can strip away the humanity of those involved. It also underscores the importance of privacy and authenticity in leading a meaningful life.